2022
DOI: 10.1002/aesr.202200098
|View full text |Cite
|
Sign up to set email alerts
|

Size Effect in SnO2/Al2O3 Core/Shell Nanowires after Battery Cycling

Abstract: Full utilization of the high storage capacity of conversion electrode materials as tin oxide (SnO2) in lithium‐ion batteries is hindered by the high volumetric expansion due to the high lithium storability which can lead to major cell damage and consequent safety issues. To overcome this issue, two promising approaches, nanostructures and buffer layers, are combined and evaluated. SnO2 nanowires (NWs) are coated with an aluminum oxide (Al2O3) buffer layer to investigate the combination SnO2–Al2O3. Strong diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 78 publications
(170 reference statements)
3
4
0
Order By: Relevance
“…The SEM images of as-prepared and postmortem SnO 2 NWs are included in Figure a,b: from the comparison of the as-prepared and postmortem uncoated SnO 2 NWs, we found that the NW morphology is maintained after cycling (Figure a,b). This is consistent with literature results of charge/discharge cycled SnO 2 NWs from ref , which showed that the wire-like structure was maintained although the crystalline structure became amorphized. However, the coated structures in Figure c–f showed more dramatic structural changes, although the initial wire-like structure can be still seen but an irregular surface has formed.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The SEM images of as-prepared and postmortem SnO 2 NWs are included in Figure a,b: from the comparison of the as-prepared and postmortem uncoated SnO 2 NWs, we found that the NW morphology is maintained after cycling (Figure a,b). This is consistent with literature results of charge/discharge cycled SnO 2 NWs from ref , which showed that the wire-like structure was maintained although the crystalline structure became amorphized. However, the coated structures in Figure c–f showed more dramatic structural changes, although the initial wire-like structure can be still seen but an irregular surface has formed.…”
Section: Resultssupporting
confidence: 93%
“…The observed material response of SnO 2 /ZnO core/shell NWs on the charge/discharge cycling in LIBs is unlike the material response of uncoated SnO 2 NWs. For these, we recently showed by TEM that the general wire-shaped structure was maintained, although the wire became amorphous with large Sn-rich areas within the NW structure . This observation agreed with the expected charge response of SnO 2 , i.e., the formation of Li 4.4 Sn surrounded by a Li 2 O matrix in the fully charged state .…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…It is important to note that the normal vector of the growth front does not have to be parallel to the NW axis but can be tilted to it . For SnO 2 NWs, the growth front of the {301} SnO 2 was reported already in the literature. ,, The projection of the normal vector of this plane onto the (011̅) SnO 2 plane, which is the SnO 2 plane at the SnO 2 –Al 2 O 3 interface, is parallel to the NW axis along [011] SnO 2 . , Hence, we would expect the same growth front for the analyzed laterally aligned SnO 2 NWs on r-plane sapphire. The following boundary conditions for the abrupt formation of a (complete) SnO 2 lattice plane during the plane-wise VLS growth of laterally aligned NWs can be defined with the above findings: SnO 2 –Au (l) interface: energy minimization SnO 2 NW (two-dimensional SnO 2 –SnO 2 homoepitaxy) SnO 2 facet edges (edges of growth front) 3 facet edges: no restrictions (NW surface and sidewalls) 1 facet edge: optimum lattice match at SnO 2 –Al 2 O 3 edge (one-dimensional SnO 2 –Al 2 O 3 heteroepitaxy) …”
Section: Resultsmentioning
confidence: 87%